Structural and biofunctional evaluation of decellularized jellyfish matrices. Issue 16 (17th April 2023) - Zhao, Jie; Yu, Wenjun; Zhang, Qi; Li, Xiaojing; Huang, Yongjie; Zhao, Suwen; Li, Tao; Liu, Shanshan; Li, Yang; Shan, Hong
Abstract : Jellyfish tissues were decellularized and assessed for intactness in the collagen triple-helix structure. The decellularized matrix can be utilized as a scaffold for culturing different types of mammalian cells and repairing injured tissues. Abstract : Extracellular matrices decellularized from marine animal tissues are emerging scaffolds in tissue engineering. Jellyfish tissues are suitable for making functional and safe decellularized matrices in part due to their simple structure, high water content, and low risk of pathogen transmission to humans. Jellyfish are some of the most prevalent marine animals, but their decellularized matrices have remained largely undeveloped. Here we evaluated the structures and functions of the jellyfish ( Rhopilema esculentum ) matrices decellularized with seven different detergents. All of them showed effectiveness in removing the cellular components. Scanning electron microscopy and mechanical testing revealed that the decellularized matrices mostly retained the native microstructures, whereas only SDS and SNL distorted the matrices' multilayered and fibrous architecture. The collagen hybridizing peptide fluorescence staining showed that SDS, SNL, Triton X-100, IGEPAL, and Tween-20 denatured the jellyfish collagen molecules to varying degrees while CHAPS and SD protected the collagen's triple-helix conformation. We demonstrated that the decellularized jellyfish matrices showed similarity to different types of mammalian collagen and supported the adhesion and proliferation of human dermal and corneal fibroblasts and mouse chondrocytes in 3D culture. Importantly, the decellularized jellyfish matrix also facilitated wound healing in vivo by reducing inflammation while promoting angiogenesis and tissue remodeling. Taken together, our study demonstrated that the decellularized jellyfish matrices are an easy-to-prepare, biocompatible, and potentially widely applicable scaffold for regenerative medicine.